Children are not like other loads: a cross-cultural perspective on the influence of burdens and companionship on human walking - Bouterse, Leah; Wall-Scheffler, Cara (PeerJ, 2018)
A major portion of humans’ activity-based energy expenditure is taken up by locomotion, particularly walking. Walking behaviors have energetic outcomes and as such can be important windows into how populations and groups adjust to different environmental and task constraints. While sex differences in the speed of paired walkers have been established by others, the dynamics of how walkers adjust their speed in more varied groups and in groups containing children remains unexplored. Furthermore, little ecological data exists to illustrate the relationships between walking speed and child-carrying. Here, we aim to determine how culture impacts the effects of group composition and infant-carrying on walking speed. Because the determinants of group dynamics and parental investment are partially cultural, we examine walking behavior in the Northwestern United States and in Central Uganda. Using an observational method, we recorded the speed, load carriage, and group composition of pedestrians in a single naturalistic urban environment within each country. Our data suggest that children are treated fundamentally differently than other loads or the presence of walking partners, and that major speed adjustments are child-dependent. Our data furthermore indicate that Ugandans walk more slowly in groups than when alone, while Americans walk more quickly in groups. Clear distinctions between the groups make large generalizations about walking behavior difficult, and highlight the importance of culturally specific contexts.
Keywords: Energetics; Cost of transport; Baby carrying; Sociality; Group mobility